Best practice of identification and proteomic analysis of extracellular vesicles in human health and disease. (2nd December 2017) - Sódar, Barbara W.; Kovács, Árpád; Visnovitz, Tamás; Pállinger, Éva; Vékey, Károly; Pocsfalvi, Gabriella; Turiák, Lilla; Buzás, Edit I
ABSTRACT: Introduction : Extracellular vesicles are emerging sources of biomarkers for modern preventive and precision medicine. Extracellular vesicles in body fluids offer a unique opportunity for integrative biomarker approaches due to their complex biocargo that includes proteins, lipids, nucleic acids and metabolites. Mass spectrometry-based proteomics data suggest that a significant portion of human proteins are sorted into extracellular vesicles and amenable for biomarker discovery schemes. Areas covered : this review focuses on key aspects of isolation, quality control and subsequent analysis of blood plasma- and conditioned medium-derived extracellular vesicle proteins, and summarizes the current state-of-the-art in the field. Furthermore, it provides introduction and guidelines for mass spectrometry-based proteomic analysis of extracellular vesicles. Expert commentary : Comparison of newly developed isolation and purification techniques with classical ultracentrifugation-based approaches are highly recommended. It is also essential to use multiple analytical approaches to characterize the isolated extracellular vesicles prior to characterization of their biocargo. Rigor in data reproducibility, critical data analysis, awareness of potential pitfalls, standardization and benchmarking are required for extracellular vesicle research to fulfil the current expectation that these subcellular structures can become a valid source of next generation biomarkers.